2014
DOI: 10.5751/es-06896-190426
|View full text |Cite
|
Sign up to set email alerts
|

Culture, Nature, and the Valuation of Ecosystem Services in Northern Namibia

Abstract: Defining culture as shared knowledge, values, and practices, we introduce an anthropological concept of culture to the ecosystem-service debate. In doing so, we shift the focus from an analysis of culture as a residual category including recreational and aesthetic experiences to an analysis of processes that underlie the valuation of nature in general. The empirical analysis draws on ethnographic fieldwork conducted along the Okavango River in northern Namibia to demonstrate which landscape units local populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 33 publications
0
14
0
1
Order By: Relevance
“…The important issue of culture and valuation of ES has been discussed in recent papers Chan 2012, Schnegg et al 2014). Schnegg et al (2014) concluded that whether or not local inhabitants' valuations converge with those from other social groups such as planners and scientists, remains an empirical question and that resolving potential differences among their views is likely to be a political, scientific, and epistemological challenge. In our present study, participants from the Mapuche culture stated values that clearly differed from those of the other two groups (Table 3, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The important issue of culture and valuation of ES has been discussed in recent papers Chan 2012, Schnegg et al 2014). Schnegg et al (2014) concluded that whether or not local inhabitants' valuations converge with those from other social groups such as planners and scientists, remains an empirical question and that resolving potential differences among their views is likely to be a political, scientific, and epistemological challenge. In our present study, participants from the Mapuche culture stated values that clearly differed from those of the other two groups (Table 3, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We found that education and recreation are the two most prevalent CES categories in the region, and conversely, aesthetics and cultural heritage appear to be the least widespread CES categories across both land cover types and resguardos (Figure 2, Figure 4 and Figure 5(b)). Participants might perceive less provisioning of aesthetics and cultural heritage CES as they may become intertwined with other CES or ES in certain places (Schnegg et al 2014). Alternatively, there might be overlap between services types, as people cannot easily distinguish between them (Plieninger et al 2013).…”
Section: Identification Of the Most Important Ecosystem Servicesmentioning
confidence: 99%
“…Studies incorporating community stakeholders' knowledge have also been conducted in Africa (Chalmers and Fabricius 2007;Fagerholm and Käyhkö 2009;Sileshi et al 2009;Fagerholm et al 2012;Schnegg et al 2014) All the aforementioned studies demonstrate that traditional knowledge should be a key component of decision-making. They also show the importance of identifying in which ecological features are associated with the cultural heritage values of stakeholders in a given cultural context and how changes in these features could affect those values.…”
Section: Introductionmentioning
confidence: 99%
“…Conservation initiatives increasingly use ecosystem service frameworks to render tropical forest landscapes and their peoples legible to market-oriented schemes such as REDD+, PES, and biodiversity offsetting in terms of the provisioning, e.g., food and water; regulating, e.g., climate and disease; supporting, e.g., nutrient cycling and pollination; and cultural, e.g., spiritual and recreational, benefits they confer to society (Costanza et al 1997, MEA 2005, Armsworth et al 2007, Naidoo et al 2008, Corbera 2012. Ecosystem service approaches have been widely criticized by scholars in the social sciences and humanities, however, for their narrow focus on a small number of easily quantifiable and marketable services and a reductionist and sometimes simplistic approach to culture (Robertson 2011, Dempsey and Robertson 2012, Kirchhoff 2012, McAfee 2012, Pröpper and Haupts 2014, Schnegg et al 2014, Winthrop 2014, Plieninger et al 2015. A major problem is the assumption that cultural services can be quantified, and then be correlated to ecological structures and functions (Daniel et al 2012, Russell et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Non-Western peoples often do not separate nature and culture as does the Western lay and scientific thinking behind ecosystem services frameworks (Ingold 2000, Latour 2009, Viveiros de Castro 2012, Descola 2013. Forms of cultural valuation can be fundamentally different to economic valuation, more of a "processual activity of meaning-making" rather than something commensurable to a market assigned monetary value (Pröpper and Haupts 2014, Winthrop 2014, Schnegg et al 2014. It is now recognized in the conservation literature that understanding the cultural valuation of biodiversity requires interpretivist as well as positivist social science theory and methods (Adams 2007, Sandbrook et al 2013, Moon and Blackman 2014.…”
Section: Introductionmentioning
confidence: 99%